1990
DOI: 10.1523/jneurosci.10-11-03653.1990
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of substance P aminoterminal heptapeptide [SP(1-7)] to mouse brain and spinal cord membranes

Abstract: Aminoterminal fragments of substance P (SP) have been previously shown to produce effects distinct, and often opposite, from those produced by the C-terminal of SP. The present investigation was initiated to determine whether N-terminal fragments interact at binding sites distinct from the neurokinin-1 (NK-1) receptor where the C-terminal sequence of SP binds with high affinity, and distinct from mu-opiate receptors, where we have previously shown the N-terminal sequence of SP to interact. A tritium-labeled am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…This observation indicated that the SP(1-7) binding in the spinal cord was due to G-protein coupled receptors specific for the heptapeptide. The presence of specific binding sites for SP (1)(2)(3)(4)(5)(6)(7) in mice brain and spinal cord has also been demonstrated [71]. …”
Section: Conversion Reactions In the Substance P Systemmentioning
confidence: 89%
“…This observation indicated that the SP(1-7) binding in the spinal cord was due to G-protein coupled receptors specific for the heptapeptide. The presence of specific binding sites for SP (1)(2)(3)(4)(5)(6)(7) in mice brain and spinal cord has also been demonstrated [71]. …”
Section: Conversion Reactions In the Substance P Systemmentioning
confidence: 89%
“…Furthermore, unlike substance P or Phe‐Gly‐Leu‐Met‐NH 2 , Gly‐Leu‐Met‐NH 2 , the tachykinin C‐terminal sequence of 3 amino‐acids, did not demonstrate any synergistic effect with IGF‐1. On the other hand, most of the biological effects of substance P have been thought to be mediated by the C‐terminal of substance P, but the N‐terminal of substance P, such as substance P (1–7), also has been shown to produce biological effects and often has produced effects opposite from those produced by the C‐terminal of substance P ( Hall & Stewart, 1984 ; Igwe et al ., 1990 ; Larson & Sun, 1992 ; Yukhanaov & Larson, 1994 ). Substance P (1–7) did not, however, demonstrate any synergistic effect with IGF‐1.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that decreased anxiety-like behavior after administration of both SP, an endogenous agonist at NK-1 receptors, and NK-1 receptor antagonists may be a function of the different dose ranges (e.g., 1-7 nmol SP versus 100-500 nmol of the NK-1 antagonists FK 888 and SR 48968; Teixeira et al 1996) or different routes of administration (e.g., oral, File 1997) in the different studies. Alternatively, anxiolytic effects of ICV administration of low doses of SP in the present experiments may have been mediated by the amino-terminus metabolite fragment of SP, SP(1-7), which may act on different receptor sites (e.g., Igwe et al 1990;Kreeger and Larson 1996).…”
Section: Discussionmentioning
confidence: 86%